Risk Factors for Hearing Loss in the Railway Transportation Sector: Literature Review - Muhammad Rinaldo; Robiana Modjo (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Hearing loss, a significant global health problem, can significantly impact quality of life. The railway sector, with its high noise levels, is particularly vulnerable. To address this, it is crucial to focus on mitigating risk factors through noise control, PPE promotion, and regular hearing assessments. Objective: The study aims to identify factors related to hearing loss in railway sectors. By understanding these factors, the research seeks to contribute to improved workplace safety and hearing conservation programs. Method: This study employed a literature review methodology, utilizing sources from Scopus and Google Scholar. Articles were searched using the keywords "hearing loss," "NIHL," "hearing impairment," "railway transport," "railway industry," and "train transportation" published within the last 10 years from 2014 to 2024. Result: The result of the article search revealed 10 articels that match the criteria set. The result show that various factors were identified that can increase the risk of hearing loss in the railway sector. Overall, risk factors for hearing loss among workers include duration of noise exposure, age, sex, individual habits, and the use of personal protective equipment (PPE). Conclusion: The need for comprehensive hearing conservation programs in the railway sector that address not only noise control, but also individual risk factors and the effective use of personal protective equipment. Further research is needed to investigate the long-term effects of combined noise and vibration exposure and the potential benefits of advanced audiometric techniques in the early detection and prevention of hearing loss.